The Contribution of Weight Status to Black-White Differences in Mortality. (3rd July 2017) - Elo, Irma T.; Mehta, Neil; Preston, Samuel
ABSTRACT: This article examines the contribution of weight status to black-white (B-W) differences in mortality at ages 40–79 using data from the National Health and Nutrition Examination Survey. We measured body mass index (BMI) based on the highest BMI attained and contrasted the contribution of BMI to that of smoking and educational attainment. We estimated both additive and multiplicative models. In addition to estimating regression coefficients we asked what would happen to B-W differences in mortality if blacks had the BMI distribution of whites, the smoking prevalence of whites, or the educational distribution of whites. B-W differences in BMI account for close to 30 percent of the B-W difference in female mortality but only about 1 percent of the B-W difference in male mortality at ages 40–79. In contrast, smoking makes a much larger contribution to the B-W difference in male (17 percent) than female (6 percent) mortality. Differences in educational attainment in turn explain 19 to 25 percent of the B-W mortality difference among men and women, respectively. Our results underscore the importance of two key risk factors as well as educational attainment in generating B-W differences in mortality.